Effects of nitric oxide associated with expression of some genes at embryonic stage of avian development - Vladimir Y. Titov; Ivan I. Kochish; Olga V. Myasnikova; Anna M. Dolgorukova; Maria A. Zaytseva; Pyotr S. Romanov; Harutyun R. Vardanyan (RUDN Journal of Agronomy and Animal Industries)
Data obtained by various researchers indicate the effect of nitric oxide (NO) on expression of some genes, in particular, the genes associated with myogenesis in birds. But until now it has not been possible to quantify this effect and possibility of its use, since the control of content of NO metabolites in tissues presented a methodological difficulty. The purpose of this research was to find out relationship between the NO content in tissues of avian embryos and the expression of genes responsible for myogenesis at various stages of embryogenesis. We used a highly sensitive and highly specifi enzyme sensor to determine the content of the main NO metabolites in tissues. Gene expression was determined by PCR-RT. The relationship between the NO content in tissues and the expression of 7 genes involved in the process of myogenesis was studied in chicken and quail embryos. There are the genes of myocyte proliferation factor 2c (mef 2c), myogenic differentiation 1 (MyoD1), myogenesis factor 5 (myf 5), myosin (mhy 1), myogenin (myog), somatostatin (MSTN), gonadotropin hormone (GHR). Blocking the synthesis of NO, which leads to a decrease in deposited NO in tissues by 5070%, results in a change in expression of most of the studied genes. Basically, there was a decrease in gene expression, in particular, myostatin (MSTN), which is responsible for suppressing growth and differentiation of muscle tissue. Thus, nitric oxide in an avian embryo can primarily play the role of regulator of muscle tissue growth, which is important for fast-growing breeds since myoblast proliferation occurs at embryonic stage of development. Regulation can be carried out by activating the mechanisms of oxidation of NO to nitrate which occurs in the embryos of fast-growing breeds.